2014
DOI: 10.1016/j.jalz.2013.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of inflammation is altered in Alzheimer's disease

Abstract: Background Resolution is the final stage of the inflammatory response, when restoration of tissue occurs. Failure may lead to chronic neuroinflammation, known as part of pathology in Alzheimer’s disease (AD) brain. Methods Specialized pro-resolving mediators (SPMs), receptors, biosynthetic enzyme, and downstream effectors involved in resolution were analyzed in post mortem hippocampal tissue from AD-patients and non-AD subjects. SPMs were analyzed in cerebrospinal fluid (CSF). Results Presence of SPMs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
283
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(303 citation statements)
references
References 47 publications
16
283
0
4
Order By: Relevance
“…Upon binding to their specifi c receptors, SPMs downregulate proinfl ammatory signals and promote the healing process of the tissue ( 11 ). Recent studies have indicated that resolution of infl ammation is disturbed in AD ( 12,13 ) and AD-related models (14)(15)(16). Treatment with one of the SPMs, lipoxin A 4 (LXA 4 ), has been demonstrated to rescue synaptic loss and reduce AD-like pathologies in transgenic AD mouse models ( 17,18 ).…”
Section: Pbmc Preparation and Ex Vivo Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon binding to their specifi c receptors, SPMs downregulate proinfl ammatory signals and promote the healing process of the tissue ( 11 ). Recent studies have indicated that resolution of infl ammation is disturbed in AD ( 12,13 ) and AD-related models (14)(15)(16). Treatment with one of the SPMs, lipoxin A 4 (LXA 4 ), has been demonstrated to rescue synaptic loss and reduce AD-like pathologies in transgenic AD mouse models ( 17,18 ).…”
Section: Pbmc Preparation and Ex Vivo Experimentsmentioning
confidence: 99%
“…Interestingly, A ␤ 40 was shown to decrease the production of the anti-infl ammatory cytokine interleukin (IL)-10 by PBMCs from AD patients ( 28 ). IL-10 has been shown to be decreased in the hippocampus of AD patients ( 13 ). Thus, the effect of A ␤ 40 on PBMCs indicates its ability to impair anti-infl ammatory signaling in a way that is relevant to AD, in addition to its well-known proinfl ammatory properties.…”
Section: Pbmc Preparation and Ex Vivo Experimentsmentioning
confidence: 99%
“…To support this notion, while proinflammatory stimuli such as LPS promoted resolvin pathways activation in microglia, Aβ42 had an opposite or insignificant effect suggesting that pro-resolutive pathways are impaired in AD (Zhu et al, 2015). This is further substantiated by the observation that the lipoxin A4 (LXA4) level is decreased in postmortem brain tissue and cerebrospinal fluid samples from AD patients (Wang et al, 2015b). Very recently, it was shown that upon Aβ40 exposure, peripheral blood mononuclear cells from AD patients secreted less LXA4 and RvD1 together with the disease progression.…”
Section: How Do N-3 Pufa Mechanisms Control Neuroinflammation?mentioning
confidence: 94%
“…A defective regulation of inflammatory responses in AD brains has been recently found; such impairment also correlated with patient cognitive performances [29]. Brain inflammation markers were also found elevated in cerebral spinal fluid (CSF) from preclinical AD [30].…”
Section: Brain Immunity and Admentioning
confidence: 97%